Activités cycloniques et nouveaux risques dans le golfe d’Aden - Jean-Philippe Cherel; Bouh Omar Ali; Moustapha Nour Ayeh; Freddy Vinet (EchoGéo)
The Gulf of Aden regions, which are experiencing quite permanent high pressures, are theoretically outside the areas affected by tropical cyclones. However, the analysis of data over the past 40 years identifies 30 tropical cyclones or depressions that have affected the region. More remarkably, their impact seems to increase significantly, as does their intensity. However, it is not clear whether this upsurge is due to global warming as the climate mechanisms on this small basin are complex. The low resilience of countries in the region facing weather events is revealed by the impact of Cyclone Sagar on 19 and 20 May 2018 in Djibouti. Although downgraded to a tropical storm, Sagar triggered two fatalities. It flooded and damaged more than 40% of the population of the main town of Republic of Djibouti (i.e. more than 200,000 inhabitants). This disaster clearly shows the unpreparedness of such poor city under arid climate in developing countries.